2019
DOI: 10.1186/s13098-019-0432-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rosiglitazone on inflammatory cytokines and oxidative stress after intensive insulin therapy in patients with newly diagnosed type 2 diabetes

Abstract: Objective To evaluate the effect of insulin sensitizer on inflammatory cytokines and oxidative stress in patients with newly diagnosed type 2 diabetes mellitus (T2DM). Methods After intensive insulin therapy, patients with newly diagnosed T2DM were continuously treated with either insulin sensitizer or insulin for 48 weeks, and then their inflammatory cytokine and oxidative stress levels were measured. Results Tumor necrosis factor alpha (TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 51 publications
3
17
0
Order By: Relevance
“…Used in this study as a positive control; rosiglitazone has been demonstrated to enhance insulin sensitivity [45]. Additionally, rosiglitazone also ameliorates oxidative stress and inflammation by reducing MDA level, enhancing SOD activity and total antioxidant capacity, as well as decreasing TNF-α and IL-6 level in the diabetic patient [46]. On the other hand, rosiglitazone has been reported to associate with cardiovascular diseases [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Used in this study as a positive control; rosiglitazone has been demonstrated to enhance insulin sensitivity [45]. Additionally, rosiglitazone also ameliorates oxidative stress and inflammation by reducing MDA level, enhancing SOD activity and total antioxidant capacity, as well as decreasing TNF-α and IL-6 level in the diabetic patient [46]. On the other hand, rosiglitazone has been reported to associate with cardiovascular diseases [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Mice were randomly divided into 6 groups (6 mice in each group) including the normal control group (without DSS treatment) treated with saline, and five colitis groups respectively treated with saline, free RLZ, RLZ loaded Ox-CD NPs (RN), blank membrane coated Ox-CD NPs (MN), and RLZ-loaded membrane coated Ox-CD NPs (RMN) with all formulations dissolved or suspended in saline. All treatment groups were given the same amount of RLZ (10 mg/kg) 34 or blank NPs intravenously via tail vein on Day 0, 3 and 5 (three times totally) according to a modified literature treatment plan 35 with the first injection set on Day 0 (6 hours after the initial DSS treatment) to exploit the therapeutic potential of RLZ at the early stage of inflammation 36 . At the same time, the injection frequency was increased accordingly as the inflammation was aggravated over time.…”
Section: Methodsmentioning
confidence: 99%
“…Several anti-inflammatory drugs including metformin, thiazolidinediones, etc., are widely used to suppress inflammation and thus insulin resistance in type 2 diabetic patients [ 10 , 11 , 12 ]; however, their long term administration is highly limited due to adverse side effects. This pathetic scenario has forced the researchers and clinicians to think of using natural drugs to target the inflammatory milieu and insulin resistance.…”
Section: Introductionmentioning
confidence: 99%